Monopole Antenna with Modify Ground Plane - rajoriya, kamal raj singh; Singhal, P.K. (International Journal of Engineering and Technology, 2012)
This paper presents on modified the ground plane of monopole antenna with varying the shape and length. Basically the length of ground plane of monopole antenna is equal and greater than ?/4. Here analyzed a different ground plane of monopole antenna that is provided an efficient bandwidth with sufficient return loss.